语序类型学视角下语言背景为英语、泰语、哈萨克语和吉尔吉斯语的汉语学习者汉语介词框架“在+N/NP+上/中”习得的偏误分析 - Noramon Sapermsup (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2024)
This article discusses the impact of language types on the second language learning. Research studies, especially, from the perspective of the type of word order in the sentences. The author compares VO (English and Thai) and OV (Kazakh and Kyrgyz) with their respective structures of prepositional frames. “At+N/NP+above/middle” in Chinese by analyzing the distinctive characteristics of each types between them. Then, propose an assumption about the relationship between different word ordering and mistakes in word order. The research results show that, in terms of word order in the sentences, although the Kazakh and Kyrgyz languages are greatly different from English and Thai, it shows similar mistakes of the VO language. This shows that the mistakes are not only related to the language type between the mother tongue and the target language. They are also related to the types of other languages they have studied before; Finally, this article provides recommendations for teaching and learning to help better understand the complexities of language learning, especially, the comparison and influence between different language types.